PERAN SEKOLAH DALAM PENDIDIKAN POLITIK BAGI SISWA DI SEKOLAH MENENGAH ATAS ISLAM HIDAYATULLAH SEMARANG - Rayi Aik Mutia; Wiwik Widayanti; Puji Astuti (Journal of Politic and Government Studies, 2015)
The school is one place to acquire science education, and special skills. In a joint life of the nation, political knowledge is absolutely necessary. Given fungsis school as the main educational institutions, political education should also be performed at the level of basic education to middle to provide sufficient political knowledge for students, giving rise to a patriotic attitude, love of the homeland, tolerance, and the nationalist spirit. In this study, researchers conducted research at Hidayatullah Islamic Senior High School of Semarang. reasons for choosing this school is based on Islamic religious schools will usually have hours of lessons associated with less religious are more than public schools. We aimed to determine how the value of political-use values are closely related to religious values.Issues to be addressed is how the role of the school in political education for students. The research method chosen this time is qualitative-descriptive type to illustrate how the role of the school in the political education of their students.From the research, it is known that political education at Hidayatullah Islamic Senior High School of Semarang more done by coaching characteror in other words is character that is supported by the enrichment of religious practices such as pra yer in congregation, dhikr, mentoring, and the Koran. Subjects that have the elements of Political Education Subjects include Civics, History, Islamic Education, Sociology, and Indonesian. Political education is also done through extracurricular activities and intra followed students as student council, MPK, Scouts, and Paskibra.Recommendations can be given by the researchers in this study is to increase the role of teachers in improving student understanding in politics. Teachers must be able to facilitate the students for discussion, role playing, demonstrating an election, political debate and so that learning becomes interesting, creative, innovative and effective. In addition, there should be a method or strategy in classifying students in the organization in accordance with the interests and talents of each.